Growth of Highly Conformal TiCx Films Using Atomic Layer Deposition Technique. Issue 4 (22nd March 2013) - Hong, Tae Eun; Choi, Sang‐Kyung; Kim, Soo‐Hyun; Cheon, Taehoon; Sunichi, H.
<x xml:space="preserve">Abstract</x> TiCx films were deposited by atomic layer deposition using tetrakis–neopentyl–titanium [Ti(CH2C(CH3)3)4] and H2 plasma as the precursor and reactant, respectively. The growth of the rock‐salt–structured TiCx films was confirmed by X‐ray and electron diffraction. The C‐to‐Ti ratio determined by Rutherford backscattering spectrometry was ~0.52 and the film resistivity was as low as ~600 μΩ cm with a high density of 4.41 g/cm3. The step coverage was approximately 90% over the trench structure (top opening diameter of 25 nm) with an aspect ratio of ~4.5.